Do ESG scores have incremental information value on the primary bond market?——evidence from China - Zhang, Chunqiang; Gao, Lu; Wang, Wenbing; Chen, Xiaojun; An, Jiapeng (Frontiers in Environmental Science, 2023)
ESG scores are essential information tools in the capital market, but prior study has not fully discussed the effect and internal mechanism of ESG scores on bond investors’ risk pricing in the primary market. The purpose of this study is to investigate the relationship between the ESG scores and risk premium of bond issuance based on the sample of Chinese listed corporations. We find that when ESG scores of the bond issuer are higher, the investors will require a lower risk premium. The result indicates that ESG scores already have positive information effect in Chinese primary bond market. Furthermore, we make mechanism and heterogeneity tests to prove that ESG scores can provide investors with incremental information, which is helpful for bond investors to identify risks and price effectively. Our study in the context of the emerging economy of China examines the incremental information value of ESG scores for bond investors, and provides evidence for the application of sustainable development concepts in global capital markets.